Faktor Yang Berhubungan Dengan Kejadian Unfase Action Pada Petugas Kebersihan - Asih Media Yuniarti (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2020)
The accidents at work are 80% of caused by unsafe action (unsafe action). K3 actors must improve OHS management which can be achieved by focusing more on unsafe actions so that the potential for work accidents can be reduced. The effort to minimize is by implementing occupational safety and health, to protect everyone around the workplace. The purpose of this study was to determine the factors associated with unsafe action on cleaning workers. And it is an analytic observational study with cross sectional design. The population of this study were all cleaning officers in RSU Sido Waras. Total population of cleaners is 50 people. a sample of 44 people. Sampling with proportional random sampling was processed through the editing, coding, scoring and tabulating stages then analyzed using the chi-square test. The results showed that 24 respondents had sufficient knowledge, 30 respondents had negative attitudes, 27 respondents were not safe. Chi square test results show that there is a relationship between knowledge and unsafe action Sig. 0.003 <α 0.05. there is a relationship between attitude and unsafe action Sig. 0.017 <α 0.05. It is hoped that the hospital will be more strict in monitoring K3 regulations, providing PPE facilities according to the dangers of the work place and socializing the scope of K3 so that they will know more by providing posters, K3 signs and others.